2003
DOI: 10.1080/0142591031000148597
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of experimental data on diffuse solar radiation in Athens, Greece, for building applications

Abstract: Proper design and performance prediction of solar energy systems requires accurate information on the availability of solar radiation. The diffuse-to-total radiation correlation, originally developed by Liu and Jordan, has been extensively used as the technique and provided excellent results, although it was latitude dependent and not universally applicable. Thus, diffuse fraction correlations of this type have been developed by few other authors and for different location. This paper presents an analysis of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 8 publications
0
29
0
1
Order By: Relevance
“…Models adjusted to data acquired in Europe are mainly linked to Northern, Central or, more recently, Mediterranean areas (e.g. : Skartveit et al (1998);Reindl et al (1990); Karatasou et al (2003); Miguel et al (2001)). To the authors' knowledge, there are no published studies focused in Azores or in any place with similar climate/cloud characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Models adjusted to data acquired in Europe are mainly linked to Northern, Central or, more recently, Mediterranean areas (e.g. : Skartveit et al (1998);Reindl et al (1990); Karatasou et al (2003); Miguel et al (2001)). To the authors' knowledge, there are no published studies focused in Azores or in any place with similar climate/cloud characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…These quantities are highly correlated with different functions established on the subject, such as piecewise linear [2], piecewise 4 th -order polynomial [5], piecewise 3 rd -order polynomial [6], piecewise 2 nd -order polynomial [7], logistic [8]. The logistic function is proven to be the best-fit based on Australian meteorological conditions.…”
Section: Solar Variationmentioning
confidence: 99%
“…Karatasou et al [24] suggested a third order polynomial correlation based on data gathered from Athens, Greece.…”
Section: • Erbs' Modelmentioning
confidence: 99%